Synthesis and refining of sunflower biodiesel in a cascade of continuous centrifugal contactor separators. Issue 2 (26th August 2014) - Abduh, Muhammad Yusuf; van Ulden, Wouter; van de Bovenkamp, Hendrik H.; Buntara, Teddy; Picchioni, Francesco; Manurung, Robert; Heeres, Hero J.
<x xml:space="preserve">Abstract</x> The synthesis of fatty acid methyl esters (FAME) from sunflower oil and methanol was studied in a continuous centrifugal contactor separator (CCCS) using sodium methoxide as the catalyst. The effect of relevant process variables like oil and methanol flow rate, rotational speed and catalyst concentration was investigated and modelled using non‐linear regression. Good agreement between experiments and model were obtained. At optimised conditions (oil flow rate of 31 mL/min, rotational speed of 34 Hz, catalyst concentration of 1.2%w/w and a methanol flow rate of 10 mL/min), the FAME yield was 94 mol% at a productivity of 2470 kg FAME/m3reactor.h. Proof of principle for the synthesis and subsequent refining of FAME in a cascade of two CCCS devices was also obtained. Relevant properties of the refined FAME obtained using this technology were determined and were shown to meet the ASTM specifications. Practical application: Synthesis and refining of sunflower biodiesel was successfully performed in a cascade of two CSSS devices. Besides for large scale biodiesel production, this technology has particularly potential to be applied in small mobile biodiesel units due to the compact size, robustness, flexibility in operation, and high volumetric productivity of the CCCS devices. <inline-graphic xlink:href="ark:/27927/pgh3s3zck68" content-type="ejlt201400206-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Schematic representation of the process concept for continuous synthesis and refining of sunflower biodiesel synthesis in a cascade of continuous centrifugal contactor separators.